Overcoming extended lag phase on optically pure lactic acid production from pretreated softwood solids - Campos, Joana; Almqvist, Henrik; Bao, Jie; Wallberg, Ola; Lidén, Gunnar (Frontiers in Bioengineering and Biotechnology, 2023)
Optically pure lactic acid (LA) is needed in PLA (poly-lactic acid) production to build a crystalline structure with a higher melting point of the biopolymer than that of the racemic mixture. Lignocellulosic biomass can be used as raw material for LA production, in a non-food biorefinery concept. In the present study, genetically engineered P. acidilactici ZP26 was cultivated in a simultaneous saccharification and fermentation (SSF) process using steam pretreated softwood solids as a carbon source to produce optically pure D-LA. Given the low concentrations of identifiable inhibitory compounds from sugar and lignin degradation, the fermentation rate was expected to follow the rate of enzymatic hydrolysis. However, added pretreated solids (7% on weight [w/w] of water-insoluble solids [WIS]) significantly and immediately affected the process performance, which resulted in a long lag phase (more than 40 h) before the onset of the exponential phase of the fermentation. This unexpected delay was also observed without the addition of enzymes in the SSF and in a model fermentation with glucose and pretreated solids without added enzymes. Experiments showed that it was possible to overcome the extended lag phase in the presence of pretreated softwood solids by allowing the microorganism to initiate its exponential phase in defined medium, and subsequently adding the softwood solids and enzymatic cocktail to proceed to an SSF with D-LA production.